2006
DOI: 10.1007/s10346-006-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural hazards vs human impact: an integrated methodological approach in geomorphological risk assessment on the Tursi historical site, Southern Italy

Abstract: The Tursi-Rabatana historical site is very representative of the cultural heritage of Basilicata, Southern Italy. Morphological evolution of the landscape is characterized by very intense erosive phenomena such as landslides, deep gullies, rills, and piping, which affect the perimeter of urban settlements and threaten the conservation of these sites. Rainfalls and the lithology of the substratum are the main factors to which the landscape evolution is linked, triggering landslide and linear erosion phenomena. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 12 publications
(13 reference statements)
0
42
0
1
Order By: Relevance
“…The lithology of the substratum (well-cemented sands, silt-clayey sands and subordinately sandy conglomerates) and rainfalls are the main factors to which the landscape evolution is linked. These represent the main determining elements for landslide triggering and linear erosion phenomena (Lazzari et al, 2006). In fact, morphological evolution of the sandy hillslopes on which Tursi town rises is characterized by very intense erosive phenomena such as landslides, deep gullies, rills, and piping, which affect the whole perimeter of urban settlements and threaten the conservation of these sites (Fig.…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The lithology of the substratum (well-cemented sands, silt-clayey sands and subordinately sandy conglomerates) and rainfalls are the main factors to which the landscape evolution is linked. These represent the main determining elements for landslide triggering and linear erosion phenomena (Lazzari et al, 2006). In fact, morphological evolution of the sandy hillslopes on which Tursi town rises is characterized by very intense erosive phenomena such as landslides, deep gullies, rills, and piping, which affect the whole perimeter of urban settlements and threaten the conservation of these sites (Fig.…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%
“…3). From the point of view of the process of physical degradation, the sandy facies are characterized by desiccation cracks to which the piping erosion and detachment blocks along the slopes are closely linked (Lazzari et al, 2006). In some cases large voids do not develop, but seepage erosion and running sand cause morphologically similar surface collapse phenomena (sinkholes).…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Basilicata region, an area extending for 9992 km 2 in southern Italy, is one of the most vulnerable regions over the national territory, in which nearly 50% of the towns are classified at high risk of landsliding or flooding (Clarke and Rendell, 2006;Lazzari et al, 2006;Lazzari, 2011). The area affected by flood risk is 260 km 2 (2.6% of the whole territory) and mainly includes the hilly areas and the coastal belt, which are exploited in agriculture, the main regional economic source (Piccarreta and Capolongo, 2009;Piccarreta et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Lazzari et al (2006) indicated that the integrated analysis between territorial data (geology, geomorphology and climate) and historical documents showed that the geomorphological hazard has been accentuated by the intense human activity. His work also produced evidence that the human interventions occurring during the historical period have been a determining factor in increasing the hazard level and accelerating the preexisting morphological processes.…”
Section: Introductionmentioning
confidence: 99%